Victoria Institute and Museum, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Originally established in 1892 and was first called the Royal Victoria Institute, it is today the National Museum and Art Gallery. This postcard is addressed to Miss Sadie Sawyer of Maine,United States of America and affixed is a penny Trinidad postage stamp.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historical buildings; Port of Spain; National Museum; 1909